Between dream and reality: The rehabilitation of war-disabled Belgian soldiers, 1914 – 1921 - Verstraete, Pieter (Historia y Memoria de la Educación, 2019)
In this article we aim to contribute to the growing interest in disability history, the history of education for people having a disability, and the existing historiography of the Great War. We will focus on the rehabilitation of Belgian blind and physically disabled soldiers. The article will take the ceremony for the Unknown Soldier, which was organized in the early twenties, as a starting point. Although everyone is familiar with the Congress Column of Brussels and the eternal flame burning at the tomb of the unknown soldier, few people know that it was a war blinded man who played an important role in the burial ceremony and that it were eight physically disabled soldiers who carried the unknown soldier to its final resting place. At this ceremony, a successful image of rehabilitation and re-education was implicitly created, showing that disabled soldiers could play a meaningful role in society again. This image will be shattered by a close study of a variety of sources preserved in Flemish and Brussels archives, including the State Archives, the Archives of the Royal Palace, the archives of the Royal Museum of the Armed Forces and Military History, the archives of the Belgian National Institute for Veterans and Victims of War and, the archives of the London St. Dunstan’s Institute. By referring to photographic material and personal files of Belgian disabled soldiers we will demonstrate that rehabilitation was definitely not «a walk in the park» and that for a number of soldiers rehabilitation simply was not possible. More specifically our presentation will zoom in on the ways in which the concept of rehabilitation took form in Belgian rehabilitation institutes such as the one in Boschvoorde for blind soldiers and the school of Port-Villez (France) for all disabled soldiers.